Cytogenetics Meets Genomics: Cytotaxonomy and Genomic Relationships among Color Variants of the Asian Arowana Scleropages formosus - Toma, Gustavo A.; dos Santos, Natália [UNESP]; dos Santos, Rodrigo [UNESP]; Rab, Petr; Kretschmer, Rafael; Ezaz, Tariq; Bertollo, Luiz A. C.; Liehr, Thomas; Porto-Foresti, Fábio [UNESP]; Hatanaka, Terumi; Tanomtong, Alongklod; Utsunomia, Ricardo [UNESP]; et al. (MDPI, 2023)
Scleropages formosus (Osteoglossiformes, Teleostei) represents one of the most valued ornamental fishes, yet it is critically endangered due to overexploitation and habitat destruction. This species encompasses three major color groups that naturally occur in allopatric populations, but the evolutionary and taxonomic relationships of S. formosus color varieties remain uncertain. Here, we utilized a range of molecular cytogenetic techniques to characterize the karyotypes of five S. formosus color phenotypes, which correspond to naturally occurring variants: the red ones (Super Red); the golden ones (Golden Crossback and Highback Golden); the green ones (Asian Green and Yellow Tail Silver). Additionally, we describe the satellitome of S. formosus (Highback Golden) by applying a high-throughput sequencing technology. All color phenotypes possessed the same karyotype structure 2n = 50 (8m/sm + 42st/a) and distribution of SatDNAs, but different chromosomal locations of rDNAs, which were involved in a chromosome size polymorphism. Our results show indications of population genetic structure and microstructure differences in karyotypes of the color phenotypes. However, the findings do not clearly back up the hypothesis that there are discrete lineages or evolutionary units among the color phenotypes of S. formosus, but another case of interspecific chromosome stasis cannot be excluded.
Keywords: chromosome; cytogenomics; molecular cytogenetics; Osteoglossiformes; SatDNA